Predictors of future research productivity among ophthalmology residents. (3rd April 2022) - Lin, John C; Lokhande, Anagha; Scott, Ingrid U; Greenberg, Paul B
ABSTRACT: Purpose: To investigate the characteristics of first-year ophthalmology residents associated with high research productivity in twelve years. Methods: All first-year ophthalmology residents in the United States (US) in 2009 listed by institutional websites were identified. Publications were obtained from Scopus and Google Scholar, h-indices were calculated, and medical school characteristics such as research productivity, region, rank, and average USMLE Steps 1 and 2 scores were obtained from National Institutes of Health, US Census Bureau, and US News. Results: Data were obtained on 70% (316/453) of residents; most were male, had Doctor of Medicine (MD) degrees, and graduated from medical schools in the US or Canada. Having an additional graduate degree [OR: 3.05, 95% CI: 1.07–8.67], between 1 and 3 publications [OR: 4.16, 95% CI: 2.22–7.79], or 4 or more publications [OR: 14.27, 95% CI: 3.13–64.94] were associated with higher future research productivity. Conclusion: Graduate degrees and publication count were key predictors of future research productivity among ophthalmology residents in the US.